Numerical study on the performance of improved masonry-to-timber connections in traditional masonry buildings - Araújo, Ana S. (2014)
This paper deals with a numerical study on the structural performance of masonry-to-timber connections in ancient buildings. The work is supported on an experimental campaign carried out at University of Minho, which aims at characterising a strengthening solution based on the use of injected anchors for the improvement of the connection between masonry and timber frame walls. The numerical study resorts to a detailed 3D finite element model, which reproduces the experimental test setup and proce- dure. The modelling approach adopted allows an accurate characterisation of the behaviour of all struc- tural elements, in terms of stress field and displacement distribution. The 3D model was validated against the available experimental results, which was then used to perform parametric analyses in order to eval- uate the influence of key parameters. Finally, simplified analytical approaches to estimate the strength capacity of injected anchors on masonry are presented and discussed.